2009
DOI: 10.1002/jobm.200800218
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Candida fukuyamaensis RCL‐3 and Rhodotorula mucilaginosa RCL‐11 to copper stress

Abstract: The effect of high Cu(II) concentrations on superoxide dismutase (SOD) and catalase (CAT) activity in Candida fukuyamaensis RCL-3 and Rhodotorula mucilaginosa RCL-11, previously isolated from a copper filter at a mine plant in Argentina, was studied. Addition of 0.1, 0.2 and 0.5 mM Cu(II) to the culture medium increased total SOD and CAT activity in both strains. Native polyacrylamide gel electrophoresis revealed two bands with SOD activity for C. fukuyamaensis RCL-3 and only one for R. mucilaginosa RCL-11; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
(40 reference statements)
0
16
1
Order By: Relevance
“…Intracellular accumulation of copper and morphological changes were observed, indicating that the resistance mechanism in R. mucilaginosa RCL-11 works through sequestration and extrusion of cytoplasmic copper ions (Villegas et al 2009). …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Intracellular accumulation of copper and morphological changes were observed, indicating that the resistance mechanism in R. mucilaginosa RCL-11 works through sequestration and extrusion of cytoplasmic copper ions (Villegas et al 2009). …”
Section: Resultsmentioning
confidence: 97%
“…Similarly, a diminished CuZnSOD activity is directly responsible for increased sensitivity of yeast mutant cells to oxidative stress (Irazusta et al 2010). Studies with R. mucilaginosa RCL-11 have demonstrated an increase in SOD activity when cells were exposed to increasing exposure times and copper concentrations (Villegas et al 2009). In addition, the yeast Yarrowia lipolytica was able to grow at high concentrations of copper sulfate and showed higher CuZnSOD activity under these conditions (Ito et al 2007).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The number of dark bodies in the cells increased with increasing incubation time. Scanning electron micrographs revealed that R. mucilaginosa RCL-11 cells grown in the presence of Cu(II) were larger than those grown in the absence of the heavy metal (Villegas et al 2009 ). An increase in catalase (CAT) and superoxide dismutase (SOD) activity correlated with Cu(II) concentrations was observed in R. mucilaginosa RCL-11 cells (Villegas et al 2009 ).…”
Section: Rhodototula Mucilaginosa Rcl-11mentioning
confidence: 98%
“…Similarly, a diminished CuZnSOD activity is directly responsible for increased sensitivity of yeast mutant cells to oxidative stress (Irazusta et al 2010 ). Studies with R. mucilaginosa RCL-11 have demonstrated an increase in superoxide dismutase activity when cells were exposed to increasing exposure times and copper concentrations (Villegas et al 2009 ). In addition, the yeast Yarrowia lipolytica was able to grow at high concentrations of copper sulfate and showed higher CuZnSOD activity under these conditions (Ito et al 2007 ).…”
Section: Superoxide Dismutasementioning
confidence: 98%